2010
DOI: 10.1124/dmd.110.035600
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological Evaluation of Acyl Glucuronides of Nonsteroidal Anti-Inflammatory Drugs Using Human Embryonic Kidney 293 Cells Stably Expressing Human UDP-Glucuronosyltransferase and Human Hepatocytes

Abstract: ABSTRACT:The chemical reactivity of acyl glucuronide (AG) has been thought to be associated with the toxic properties of drugs containing carboxylic acid moieties, but there has been no direct evidence that AG formation was related to the toxicity. In the present study, the cytotoxicity and genotoxicity of AGs were investigated. Human embryonic kidney (HEK) 293 cells stably expressing UDP-glucuronosyltransferase (UGT) 1A3 (HEK/UGT1A3) were constructed to assess the cytotoxicity of AGs, and HEK/UGT1A4 cells wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…Although there is increasing evidence that AGs form drug-protein adducts due to their chemical reactivity (Wang et al, 2001;Horng and Benet, 2013), cytotoxicity and genotoxicity of AGs have not been observed in vitro (Koga et al, 2011). Conversely, the AGs of withdrawn drugs and warning drugs that have idiosyncratic drug toxicity risks, such as zomepirac and diclofenac, induced the mRNA expression levels of immune-and inflammation-related genes in human PBMCs (Miyashita et al, 2014;Iwamura et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is increasing evidence that AGs form drug-protein adducts due to their chemical reactivity (Wang et al, 2001;Horng and Benet, 2013), cytotoxicity and genotoxicity of AGs have not been observed in vitro (Koga et al, 2011). Conversely, the AGs of withdrawn drugs and warning drugs that have idiosyncratic drug toxicity risks, such as zomepirac and diclofenac, induced the mRNA expression levels of immune-and inflammation-related genes in human PBMCs (Miyashita et al, 2014;Iwamura et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In human hepatocytes, the AGs of nonsteroidal anti-inflammatory drugs (diclofenac, naproxen, ketoprofen, and ibuprofen) were rapidly excreted and did not accumulate in the cell (Koga et al, 2011). ZP-AG is immediately exported from the liver into blood rather than bile because excretion of ZP and its metabolites into bile is a minor route in humans and laboratory animals (Grindel et al, 1980).…”
Section: Downloaded Frommentioning
confidence: 99%
“…It is well known that AGs are characterized by their electrophilic reactivity, and this reactivity is implicated in a wide range of adverse drug effects, including drug hypersensitivity reactions and cellular toxicity (Ritter, 2000). We previously revealed that the AGs of various NSAIDs, such as naproxen, diclofenac, ketoprofen, and ibuprofen, showed no direct cytotoxicity and genotoxicity in human hepatocytes and cells stably expressing human UGTs (Koga et al, 2011). Therefore, in this study, we investigated whether the AGs exert toxicity through inflammation- dmd.aspetjournals.org related responses.…”
Section: Discussionmentioning
confidence: 99%
“…We previously revealed that the NSAID AGs that were produced in the cells are efficiently released from the cells into the culture medium (Koga et al, 2011). Thus, the effect of AGs was evaluated by exposing the AGs to the outside of the cells, i.e., the culture medium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation